Surgical training in the UK: is cost a barrier to entry?. Issue 1158 (7th January 2021) - Vinnicombe, Zak; Little, Max; Super, Jonathan; Anakwe, Raymond
Abstract : Background: There is good quality evidence linking socioeconomic background and the likelihood of a surgical career. Additionally, training in surgery is more expensive than in other specialties. Our aim was to assess the awareness and perceptions of trainees and medical students of the relative costs of surgical training and to determine whether perceptions of cost deter potential surgical trainees. Methods: Medical students, foundation doctors and core trainees in England were surveyed over a 2-week period. χ 2 tests of independence were used to assess statistically significant associations between measured variables Main findings: A total of 284 responses were received. More than half of respondents (54%) were not previously aware of the high costs of surgical training. More than a quarter of respondents (27%) did not take out a student loan. There was a significant association (p=0.003) between familial income and being less likely to consider a surgical career due to the costs. Respondents who reported receipt of a student loan were also significantly less likely to consider a surgical career due to the costs (p=0.033). Conclusion: Our study demonstrates an important relationship between perceived costs of surgical training and future career aspirations. This suggests that access to surgical training may still be difficult for many. This study also highlights a general lack of awareness of high surgical training costs. It is important that surgical training is accessible. Financial status should not be a significant disincentive and widening access to surgical training can only serve to enrich and advance the specialty.